Improving antidepressant drugs: update on recently patented compounds - ROZAS, ISABEL (My University, 2009)
Background: According to the World Health Organization, depression is a common condition that affects about 121 million people worldwide. Although the pathophysiological origin of this condition is still unknown, most of the known antidepressants enhance the extracellular availability of brain monoamines (serotonin and/or noradrenaline). Objective/Method: We have searched for the potential drugs and targets being addressed in the most recent patents. Hence, we have explored the Patent Database of the European Patent Office using the esp@cenet searching engine for the period 2005-2008, looking for ?antidepressants?. In addition, a search in the Medtrack database yielded information on pharmaceutical companies developing compounds as antidepressants, market size and their market prospects. Conclusions: We have found that, in general, the preferred targets to develop antidepressants continue to be those aiming the serotoninergic system and, in a less extend, the noradrenergic one; but, more particularly, those that aim multiple targets are preferred due to problems concerning the efficacy of highly selective drugs. Additionally, a small number of new systems are being targeted, such as the melatonergic. However, when looking at the pharma-market and the antidepressants in the pipeline a new trend is observed developing dual-action drugs that could be used in depression and schizophrenia therapy.
PUBLISHED
Keywords: depression; Antidepressants